Stabilizing high aspect ratio x-ray gratings with top layer resist grid - Richter, Michael; Beckenbach, Thomas; Rauch, Constantin; Schreiner, Stephan; Zuber, Marcus; Hamann, Elias; Last, Arndt; Börner, Martin; Korvink, Jan; Meyer, Pascal (Journal of Micro-Nanolithography MEMS and MOEMS, 2024)
A problem with high aspect ratio x-ray gratings, fabricated by the deep x-ray LIGA process, is the collapse of the metallic structure when the resist is removed. A unique method that consists of positioning perpendicular metal bridges on top of the grating (roof bridges) is described and tested as a solution. First, a theoretical study is carried out on the transmission loss of such grids as a function of the thickness, their spacing, their materials (gold or nickel), and the x-ray energy. Different processes with their own advantages and disadvantages are possible and described. To further satisfy the requirement of curved gratings, two processes are tested in detail: structuring the x-ray grating with a laser and planarization followed by restructuring a second resist layer. In both cases, a second electroplating step is performed. Finally, a grating with a 12 cm bending radius and stabilization is fabricated. To assess the quality of the grids, two complementary methods are used: scanning electron microscopy and angular x-ray transmission. The latter one is an innovatively developed measurement process specially dedicated to x-ray gratings. The results for the fabrication processes are discussed and rated. The stability provided by the roof bridges works as intended, although the overall quality of the grating is slightly reduced.
CRIS-Team Scopus Importer:2024-04-12
Keywords: angular x-ray transmission; Talbot–Lau interferometry; x-ray grating; x-ray LIGA